Two new species of Chiropterotriton (Caudata: Plethodontidae) from northern Mexico - Rovito, Sean M.; Parra-Olea, Gabriela (Zootaxa, 2015)
Species of the genus Chiropterotriton are distributed through much of northern and eastern Mexico. The genus has presented taxonomic difficulties, with a number of species waiting to be described. We describe two new species, Chiropterotriton cieloensis sp. nov. and Chiropterotriton infernalis sp. nov., from the Mexican state of Tamaulipas based on both molecular and morphological data. We present a phylogenetic hypothesis for the group, with emphasis on the taxa from northern Mexico, based on mitochondrial DNA, and discuss the other species of northern Mexico, especially the wider-ranging C. multidentatus, to which the new species were formerly assigned.